Association between 2D:4D ratios and sprinting, change of direction ability, aerobic fitness, and cumulative workloads in elite youth soccer players - Nobari, H.; Eken, Ö.; Prieto-González, P.; Oliveira, R.; Brito, J. P. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The aim of this study was two-fold: (i) to determine the correlation between 2D:4D, maximal oxygen uptake (VO2max), body fat percentage (BF%), maximum heart rate (HRmax), change of direction (COD), and accumulated acute and chronic workload variables; (ii) to verify if the length of the second digit divided by fourth digit (2D:4D) can explain fitness variables and accumulated training load.